Clinical Acceptability of the Internal Gap of CAD/CAM PD-AG Crowns Using Intraoral Digital Impressions. (28th November 2016) - Kim, Tae-Gyung; Kim, Sungtae; Choi, Hyunmin; Lee, Jae-Hoon; Kim, Jae-Hong; Moon, Hong-Seok
Abstract : The purpose of this study was to compare the internal gap between CAD/CAM palladium-silver crowns and cast gold crowns generated from intraoral digital versus conventional impressions and to determine the clinical acceptability. Nickel-chrome master dies were made from the prepared resin tooth with the conventional impression method (n = 40 ). For ICC (Intraoral, CAD/CAM) group, 10 intraoral digital impressions were made, and 10 CAD/CAM crowns of a PD-AG (palladium-silver) machinable alloy were generated. For IC (Intraoral, Cast) group, 10 gold crowns were cast from ten intraoral digital impressions. For CCC (Conventional, CAD/CAM) group, 10 CAD/CAM PD-AG crowns were made using the conventional impression method. For CC (Conventional, Cast) group, 10 gold crowns were fabricated from 10 conventional impressions. One hundred magnifications of the internal gaps of each crown were measured at 50 points with an optical microscope and these values were statistically analyzed using a two-way analysis of variance (α = 0 . 05 ). The internal gap of the intraoral digital impression group was significantly larger than in the conventional impression group (P < 0.05 ). No significant difference was observed between the CAD/CAM group and the cast group (P > 0.05 ). Within the limitations of this in vitro study, crowns from intraoral digital impressions showed larger internal gap values than crowns from conventional impressions.